2015
DOI: 10.4012/dmj.2014-175
|View full text |Cite
|
Sign up to set email alerts
|

Control of hydroxyapatite crystal growth by gallic acid

Abstract: The purpose of this study is to detect the effect of gallic acid (GA) on hydroxyapatie crystal growth and find the mechanism of the regulation. We evaluated the morphology of HAP crystals grown under various amounts of GA (0, 0.05, 1, and 4 gL −1 ). Subsequently, the chemical composition, crystal size and the morphology were investigated via the energy-dispersive X-ray spectrometer, attenuated total fourier transform infrared spectroscopy, thermogravimetric analysis, X-ray diffraction analysis, transmission el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The Ca/P ratios were also calculated. The results showed that in all the groups, the main elements of the precipitate were calcium and phosphorus, and the Ca/P ratios were close to 1.67 which is consistent with the Ca/P ratio in HAP(Bei tang) 12 . The results we had observed Ca/P ratio by ICP method was approx 2.01 which was not similar to this study.It proposed that G. chinensis has anti-bacterial properties to restrain the growth and acid production of certain cariogenic bacteria, including streptococcus and lactobacillus.…”
Section: Resultssupporting
confidence: 74%
“…The Ca/P ratios were also calculated. The results showed that in all the groups, the main elements of the precipitate were calcium and phosphorus, and the Ca/P ratios were close to 1.67 which is consistent with the Ca/P ratio in HAP(Bei tang) 12 . The results we had observed Ca/P ratio by ICP method was approx 2.01 which was not similar to this study.It proposed that G. chinensis has anti-bacterial properties to restrain the growth and acid production of certain cariogenic bacteria, including streptococcus and lactobacillus.…”
Section: Resultssupporting
confidence: 74%
“…In fact, in general, polyphenols interact with hydroxyapatite by binding to the surface of the apatite crystals. This binding can affect the nucleation and growth of the apatite crystals, leading to changes in the size and shape of the crystals [ 55 , 56 ]. In any case, the surfaces had a remarkable ability to induce hydroxyapatite precipitation during soaking in simulated body fluid, as it appeared after 7 days of soaking.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that GA-HAP had an urchin-like shape, while loose needle-like crystals were found in HAP formed without additive. Accordingly, the same authors [103] investigated the morphology and the size changes of crystals as function of the GA concentration (0.05 to 4 g/L). They reported that increasing the concentration in GA reduced the crystal size from 40 to 25 nm.…”
Section: Remineralization Cell Viability and Differentiationmentioning
confidence: 99%
“…Accordingly, the same authors [ 103 ] investigated the morphology and the size changes of crystals as function of the GA concentration (0.05 to 4 g/L). They reported that increasing the concentration in GA reduced the crystal size from 40 to 25 nm.…”
Section: Hydrolysable Tannins and Gallic Acidmentioning
confidence: 99%